Evaluasi Keterlambatan Proses Pengadaan Jasa Konstruksi Pinjaman Hibah Luar Negeri Saudi Fund for Development - Setiawan, Budi; Hajji, Apif M; Ariestadi, Dian; Alfianto, Imam (Universitas Nahdlatul Ulama Blitar, 2024)
One of the financing for construction work is financing sourced from foreign loans or grants/PHLN. This type of financing model always has guidelines set by the lender/lender. The procurement implementation guidelines created by these lenders are sometimes not in line with the Goods and Services Procurement Regulations in Indonesia, giving rise to the problem of delays in procurement implementation time in searching for potential construction service providers. The aim of the research is to evaluate the influence of regulations for the procurement of construction goods and services in Indonesia on the guidelines made by SFD lenders, causing progress in the implementation of construction tenders to be delayed. The research method used is to identify variable instruments owned by researchers from primary and secondary data, which are then developed into variables and indicators and processed using the nvivo application. From the results of the data processing, it was then evaluated and validated using data from interviews conducted with several service providers with PHLN. The results of the data processing showed that there were several factors that caused the procurement process to be completed late. The first factor is the existence of procurement regulations of the Republic of Indonesia which are not in line with the lender's guidelines, the second factor is the experience of actors procuring goods and services from PHLN funding sources, the third factor is the communication factor between relevant stakeholders and the fourth is the cultural factor possessed by the lender country.